Terrain Adaptability Mechanism of Large Ruminants’ Feet on the Kinematics View - Qun Zhang; Xilun Ding; Kun Xu (Applied Bionics and Biomechanics)
Ruminants live in various parts of land. Similar cloven hooves assist ruminants in adapting to different ground environment during locomotion. This paper analyzes the general terrain adaptability of the feet of ruminants using kinematics of the equivalent mechanism model based on screw theory. Cloven hooves could adjust attitude by changing relative positions between two digits in swing phase. This function helps to choose better landing orientation. “Grasping” or “holding” a rock or other object on the ground passively provides extra adhesion force in stance phase. Ruminants could adjust the position of the metacarpophalangeal joint or metatarsophalangeal joint (MTP or MCP) with no relative motion between the tip of feet and the ground, which ensures the adhesion and dexterity in stance phase. These functions are derived from an example from chamois’ feet and several assumptions, which are believed to demonstrate the foundation of adaptation of ruminants and ensure a stable and continuous movement.